The impact of 24-h movement behaviors on college students’ physical fitness and its isotemporal substitution benefits: a compositional data analysis approach - Rongxuan Li; Di Cui; Qingqing Fan; Le Zhao; Ziyao Xia; Tianer Zuo; Ye Qiu; Qing Jiang; Jiasheng Huo; Zuoliang Wang (BMC Public Health)
Abstract Objectives This study aimed to provide theoretical and empirical support for promoting physical fitness enhancement and implementing evidence-based behavioral interventions on university campuses. Through a rigorous compositional data analysis framework combined with isotemporal substitution model (ISM), we systematically examined the associations between 24-h movement behaviors and physical fitness among college students. Methods This study employed a stratified random cluster sampling design to recruit 3,974 participants from the physical education classes at a technological university located in Central South China during the 2022–2023 academic year. Data collection comprised two standardized assessments. The 24-h movement behaviors Questionnaire (24HMBQ) was administered to quantify five critical domains of daily movement patterns: sleep (SLE), sedentary behavior (SED), light physical activity (LPA), moderate physical activity (MPA), and vigorous physical activity (VPA). The participants’ physical fitness was assesed against the Chinese National Student Physical Fitness Standards (CNPFSS). Employing compositional isotemporal substitution analysis, this study examined the dose–response relationship between 24-h movement behaviors and physical fitness in college students. Results Compositional regression analysis revealed a significant positive correlation between moderate-to-vigorous physical activity (MVPA) and the total physical fitness test score among total students, science students, male students, and male science students (all P < 0.05). MVPA exhibited consistent positive correlations with indicators in sit-and-reach, standing long jump, and pull-up tests among total students, while demonstrating a negative correlation with indicators for 50-m and 800/1000-m run (all P < 0.05). Meanwhile, LPA was found to be positively linked to indicators in vital capacity and 800/100 m run (all P < 0.05). ISM revealed that reallocating 30 min from LPA, sleep, and SED to MVPA significantly enhanced the total physical fitness test scores for science students, male students, and male science students (all P < 0.05). Furthermore, substituting 60 min of MVPA for other activity behaviors led to significant improvements in the total physical fitness test scores for the total students, as well as these three subgroups(all P < 0.05). In the dose–response analysis, a symmetrical pattern emerged when substituting MVPA for other activities, with respect to the total physical fitness test score. For the total student cohort, the substitution duration displayed a positive correlation with the test score, peaking at 50 min within the range of -40 to + 50 min. For science students, male students, and male science students, the peak correlation occurred at 45 min within the range of -40 to + 45 min. Conclusion For students in technological universities, it is imperative to enhance both MVPA and LPA, with a stronger focus on increasing MVPA. Additionally, the frequency of MVPA during 45-min physical education classes should be intensified.